Knowledge, Attitude and Behavior of Medical Students Toward Safety in Laboratory Practices - Chaicom, Kanokon; Klangsang, Pinsuda; Palaeng, Boonpeng (Srinagarind Medical Journal, 2013)
Background and Objective: Medical personnels are at risk for infection higher than the general population.The prevalence of disease carriers increased in the groups of medical doctors, dentists, nursing or medical students. Especially in the group of medical students who are at risk of accidents practices in doing the laboratory. Therefore, this study aimed to examine the knowledge, attitude and behavior and the relationship between knowledge, attitude and behavior of medical students in laboratory safety of the department of medicine, faculty of medicine. Khon Kaen university. To serve as a guide in teaching practice, management and operations, to promote safety in the operating room to be more effective. Methods: This study is a survey research, studied in 78 medical students doing practice in the department of medicine, faculty of medicine, Khon Kaen university, between September and December 2555. Data were collected during January 2555 to April 2556, using questionnaires and analyzed by SPSS for Windows using descriptive statistics. Results: The results showed that 78 medical students were females 58.50 %, average age was 22 years.(S.D.=0.65 min=20max=23). The medical students with their experience of doing laboratory practices were 88.55% and 38.25% used to have accident or injury in their works. They have a good level of knowledge, attitude and behavior of laboratory safety are 71.55%, 85.40%and 36.50% respectively. Moderate levels of knowledge, attitude and behavior of laboratory safety are 27.17%, 14.56% and 59.30% respectively. Low levels of knowledge and behavior of laboratory safety are1.28% and 4.42% respectively. Knowledge is positively related to attitude. Knowledge, positive relationship with behavior. And attitudes were positively correlated with behavior. Statistically significant at the 0.01 level. Conclusions: Knowledge, attitude and behavior of medical students in laboratory safety level is good, good and moderate respectively, Their knowledge have a positive relationship with attitude and behavior. The attitudes have a positive relationship with behavior. At statistically significant at the 0.01 level. Keywords: Safety In Student Laboratory, Medical student